Diabetes treatment and mental illness: a call for an integrated health care system in underserved semi-rural Malaysia - Thangiah, Govindamal; Johar, Hamimatunnisa; Ismail, Roshidi; Reininghaus, Ulrich; Bärnighausen, Till; Thurairajasingam, Sivakumar; Reidpath, Daniel; Su, Tin Tin (International journal of environmental research and public health, 2022)
Diabetes mellitus (DM) management imposes a tremendous psychological burden on patients. The study investigates the association between DM treatment with blood glucose (BG) control and common mental health conditions. A cross-sectional study was conducted among 1821 individuals with DM in a community-based survey conducted in 2013. Information on respondents’ sociodemographic, mental health, DM treatment, and BG levels was collected. Multinomial logistic regression was employed to examine the association of diabetes treatment with controlled BG levels (<11.1 mmol/L) (42.5%, n = 774) or uncontrolled BG levels (34.3%, n = 625) compared with those not undergoing treatment (23.2%, n = 422) on depression anxiety, and stress. Having DM treatment and controlled BG was associated with high depressive symptoms (Relative Risk Ratio, RRR: 2.42; 95% CI 1.33-4.41) and high anxiety symptoms (1.66; 1.08-2.56) but not with perceived stress. However, treated DM with uncontrolled BG was associated with anxiety (high: 1.64; 1.05-2.56; low: 2.59; 1.10-6.09) but not depression or perceived stress. Our results suggest that being treated for DM, regardless of glucose control status, was associated with anxiety symptoms, whereas being treated with controlled BG was associated with high depressive symptoms. This situation highlights the need for integrative, multidisciplinary care for DM patients with mental health comorbidities.